Impact of Remuneration and Motivation on Employee Performance Amidst The COVID-19 Pandemic - Mazlan, Adilah; Demong, Nur Atiqah Rochin (Information Management and Business Review, 2024)
Globalization and other environmental issues are causing problems for organizations. Improving employee performance is the responsibility of any organization, as it is crucial for the attainment of optimal objectives. An employee’s reputation is improved by performing well on the job, which helps them advance in their professions. Without effective remuneration and motivation, it can affect employee performance in the organization. Other than that, the past researchers regarding this study also discussed. The relationship between independent variables and dependent variables was assessed using descriptive analysis, normality analysis, reliability analysis, Pearson’s correlation analysis, and multiple regression analysis in this study. The population and sample of employees in the selected organization in Perak. The total population of 250 respondents in the company, and the sampling size was 148 respondents based on the Krejcie & Morgan table. Data collection in this study was conducted through questionnaires, and the data were analyzed using SPSS 20. The findings indicated that employee performance is significantly and positively influenced by remuneration and work motivation, with motivation being the most significant factor in the performance of education employees during the COVID-19 pandemic.